Caffeine and Cardiovascular Disease: A Scientific Statement From the American Heart Association - Gregory M. Marcus; Frank B. Hu; Rob M. van Dam; Marilyn C. Cornelis; Thomas A. Dewland; JungHee Kang; Susanna C. Larsson; Robert L. Page; Niyati Parekh (Circulation, 2026)
Caffeine is one of the most commonly consumed drugs in the world. It is found in various naturally occurring substances and can be ingested in a synthetically derived pure form. The majority of human subject–based research is observational and has focused on beverages and foods that contain caffeine. The relationships between caffeine and cardiovascular risk factors and diseases are complex, exhibiting heterogeneity depending on the nature of the caffeine consumed and individual-level propensities. Acute versus chronic caffeine-associated cardiovascular effects are often different. Most studies suggest an inverse J-shaped relationship between consumption of naturally occurring caffeinated products and blood pressure. Data on relationships between caffeine and diabetes are not consistent, but habitual coffee consumption has been associated with a lower risk of incident type 2 diabetes. Whereas no clear relationship between caffeine and blood lipids is evident, unfiltered coffee raises low-density lipoprotein cholesterol. Caffeine, studied primarily in the context of coffee, has been shown either to have no relationship or to be associated with a lower risk of coronary artery disease and heart failure. Randomized controlled trial data among regular caffeinated coffee drinkers showed that caffeinated coffee decreases the risk of atrial fibrillation occurrence but increases the frequency of premature ventricular contractions. Data are fairly consistent that moderate caffeine consumption, again studied primarily in the setting of coffee consumption, was associated with a lower risk of stroke. Data on high doses of caffeine such as that found in energy drinks are limited and generally suggest cardiovascular harm.